Response Letter to the Editor in Reference to Letter to the Editor about "Molecular Characterization of Animal Fasciola spp. Isolates from Ker-manshah, Western Iran" - Arezoo BOZORGOMID; Naser NAZARI; Eshrat Beigom KIA; Homa HAJJARAN; Mehdi MOHEBALI; Mojgan ARYAEIPOUR; Peyman HEIDARIAN; Mohammad Saeid EZATI; Mohamad Bagher ROKNI (Tehran University of Medical Sciences, 2018)
Response Letter to the Editor in Reference to Letter to the Editor about "Molecular Characterization of Animal Fasciola spp. Isolates from Ker-manshah, Western Iran"